Chronic caffeine intake increases androgenic stimuli, epithelial cell proliferation and hyperplasia in rat ventral prostate - Sarobo, Carolina [UNESP]; Lacorte, Livia M. [UNESP]; Martins, Marcela [UNESP]; Rinaldi, Jaqueline C. [UNESP]; Moroz, Andrei [UNESP]; Scarano, Wellerson R. [UNESP]; Delella, Flávia Karina [UNESP]; Felisbino, Sergio L. [UNESP] (Wiley-Blackwell, 2012)
Coffee intake has been associated with a low risk of developing cancer, including prostate cancer, which is one of the most commonly diagnosed cancer in men. However, few studies have evaluated the chronic effects of caffeine, which is the most abundant methylxanthine in coffee, on prostate morphology and physiology. In the present study, we investigated the effects of chronic, low-dose caffeine intake on rat prostate morphology from puberty to adulthood. Five-week-old male Wistar rats were randomized into two experimental groups: caffeine-treated (20 ppm in drinking water, n = 12) and control (n = 12). The ventral and dorsolateral prostates were dissected, weighted and submitted to morphological, morphometrical and immunohistochemical analysis of cellular proliferation, apoptosis and androgen receptor (AR) tissue expression. The testosterone (T) and dihydrotestosterone (DHT) concentrations were measured in the plasma. Our results show that caffeine intake increased the concentrations of T and DHT, organ weight, epithelial cell proliferation and AR tissue expression in the ventral prostatic lobe. All the ventral prostates from the caffeine-treated animals presented various degrees of epithelial and stromal hyperplasia. Our results suggest that chronic caffeine intake from puberty increases androgenic signalling and cell proliferation in the rat prostate gland and can be related to the development of benign prostatic hyperplasia.
Keywords: androgen receptor; apoptosis; caffeine; cell proliferation; hyperplasia; prostate